2020
DOI: 10.1007/s00264-020-04739-y
|View full text |Cite|
|
Sign up to set email alerts
|

Thirty-day mortality following surgical management of hip fractures during the COVID-19 pandemic: findings from a prospective multi-centre UK study

Abstract: Purpose Thirty-day mortality of patients with hip fracture is well researched and predictive; validated scoring tools have been developed (Nottingham Hip Fracture Score, NHFS). COVID-19 has significantly greater mortality in the elderly and comorbid patients which includes hip fracture patients. Non-operative treatment is not appropriate due to significantly higher mortality, and therefore, these patients are often exposed to COVID-19 in the peri-operative period. What is unclear is the effect of concomitant C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 15 publications
2
84
0
Order By: Relevance
“…Several studies have reported an increased mortality rate among patients with hip fractures who were diagnosed with COVID-19 [3,11,16,24,[27][28][29][30][31]. In this study none of the con rmed or suspected COVID-19 patients died in-hospital so the COVID-19 diagnosis may not be driving this increased risk for mortality.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Several studies have reported an increased mortality rate among patients with hip fractures who were diagnosed with COVID-19 [3,11,16,24,[27][28][29][30][31]. In this study none of the con rmed or suspected COVID-19 patients died in-hospital so the COVID-19 diagnosis may not be driving this increased risk for mortality.…”
Section: Discussionmentioning
confidence: 59%
“…Egol et al reported also no difference in the time from arrival to surgical intervention for hip fracture patients during the pandemic [23]. Alternatively Narang et al reported a signi cant increase in the proportion of patients who experienced a delay to operation during the pandemic [24]. Slullitel et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversy remains regarding the management of patients suffering a hip fracture with coronavirus infectious disease-19 in the acute preoperative phase, especially concerning the timing of surgery and perioperative measures. Narang [25] had a lower surgical delay for COVID-19( +) Fig. 2 Kaplan-Meier survival curves for the four groups described: historic controls treated in 2018-19 (black), pre-cohorting in 2020 (blue, dotted), non-COVID circuit of 2020 (green, dashed) and COVID-19 circuit of 2020 (red, solid).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, early limited evidence published so far suggests poor outcomes with high postoperative mortality in patients with a hip fracture and concomitant COVID-19 infection (available studies indicate a mortality rate greater than 30%). 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 We have undertaken a ...…”
Section: Introductionmentioning
confidence: 99%